Understanding friendship : on the moral, political, and spiritual meaning of love - Chartier, Gary (Fortress Press, 2022)
Understanding Friendship illustrates friendship as an expression of Christian love that can enrich one's life and be socially, culturally, and politically significant. The book examines what friendship is, how its distinctive moral status can be supported by multiple approaches to Christian ethics, and its part in Christian spirituality.